Autocratic checks and balances? Trust in courts and bureaucratic discretion. Issue 4 (19th May 2019) - Corduneanu-Huci, Cristina
ABSTRACT: An emerging literature in political economy focuses on democratic enclaves or pockets of quasi-democratic decision-making embedded in non-democracies. This article first explores the factors that may lead to the emergence of such institutional checks and balances in autocratic politics. I use the comparative analysis of courts in Morocco and Tunisia, and argue that interest group mobilization and the centrality of legalism in political development have been essential for the existence of "governance" enclaves. Second, I explore whether such checks effectively contain everyday rent-seeking, as well as the theoretical channels through which this may occur. Findings from firm-level surveys conducted in Morocco and Tunisia in 2013 indicate that higher general trust in courts, even in modest relative terms, rendered businesses significantly less vulnerable to tax corruption in Tunisia, in sharp contrast to the Moroccan case.